Uncoupling protein 2 expression affects androgen synthesis in polycystic ovary syndrome - Liu, Yun; Jiang, Hong; Xing, Fu-Qi; Huang, Wu-Jian; Mao, Li-Hua; He, Ling-Yun (Endocrine, 2013)
The roles of uncoupling protein-2 (UCP2) on the androgen synthesis of granulosa cells derived from patients with polycystic ovary syndrome (PCOS) and normal subjects were explored. Primary human granulosa cells from 18 patients who received in vitro fertilization (IVF) were examined; nine patients had PCOS with hyperandrogenism. Primary cultures were treated with genipin, a proton leak inhibitor, guanosine diphosphate (GDP), an UCP inhibitor, and triiodothyronine (T3), an inducer of UCP gene expression. Mitochondrial membrane potential was determined using the JC-1 assay. T3 induced P450scc and UCP2 expressions and testosterone synthesis in both normal and PCOS granulosa cells. Their expressions in response to T3 treatments were correlated in the PCOS group. Differences in testosterone synthesis were observed between normal and PCOS cells in response to genipin. Increased mitochondrial membrane potential was observed in response to genipin and GDP; while T3 decreased it. Increased ovarian UCP2 expression in response to T3 treatment in PCOS may alter pregnenolone synthesis by influencing P450scc expression, thus altering testosterone production. Further in vivo studies are necessary to fully elucidate the role of UCP2 in the hyperandrogenism commonly observed in PCOS.